Study on regioselective synthesis of bioactive bis-spiropyrazolines using molecular orbital calculations - Farghaly, Thoraya Abd El-Reheem; Abbas, Ikhlass Mohamed; Hassan, Walid Mohamed Ibrahim; Lotfy, Mai Samir (European Journal of Chemistry, 2014)
1,3-Dipolar cycloaddition reaction of (2E,2’E)-2,2’-(1,4-phenylene bis(methanylylidene)) bis(3,4-dihydronaphthalen-1(2H)-one) (3) and 2,2’-(1,4-phenylene bis(methanylylidene)) bis(1H-indene-1,3(2H)-dione) (8) with a variety of nitrilimines, generated in situ by triethylamine dehydrohalogenation of the corresponding hydrazonoyl halides, (4) proceeded region-selectively and affording novel spiropyrazoline derivatives 5 and 10, respectively. The mechanisms of the reactions studied are discussed and the structures of the products were confirmed by spectral data and elemental analyses. Also, molecular orbital plots for HOMO and LUMO verify our suggested mechanism and stereo-selectivity of the reaction. The antimicrobial activity of the products was evaluated and promising results were obtained.